Mandibular Motor Control During the Early Development of Speech and Nonspeech Behaviors. - Steeve, Roger W.; Moore, Christopher A. (Journal of Speech, Language & Hearing Research, 2009)
Purpose: The mandible is often portrayed as a primary structure of early babble production, but empiricists still need to specify (a) how mandibular motor control and kinematics vary among different types of multisyllabic babble, (b) whether chewing or jaw oscillation relies on a coordinative infrastructure that can be exploited for early types of multisyllables, and (c) whether the organization of motor control and associated kinematics varies across the nonspeech behaviors that are candidate motor stereotypies for speech. Method: Electromyographic signals were obtained from mandibular muscle groups, and associated kinematics were measured longitudinally from a typically developing infant from 9 to 22 months during jaw oscillation, chewing, and several types of early multisyllabic babble. Results: Measures of early motor control and mandibular kinematics for multisyllabic productions indicated task-dependent changes across syllable types and significant differences across babble and nonspeech behaviors. Differences in motor control were also observed across nonspeech behaviors. Conclusions: Motor control for babble appears to be influenced by the balanced interaction between developing motor and linguistic systems, such that variation in linguistic complexity systematically evinces changes in motor organization apparently to meet these demands. This same effect was noted among chewing and jaw oscillation; task-dependent changes in mandibular control were noted across behaviors. Reprinted by permission of the publisher.